If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(12) + y = 36 Multiply 3 * 12 36 + y = 36 Add '-36' to each side of the equation. 36 + -36 + y = 36 + -36 Combine like terms: 36 + -36 = 0 0 + y = 36 + -36 y = 36 + -36 Combine like terms: 36 + -36 = 0 y = 0 Solving y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 0
| 4.7m=18-2.7m | | 12k+50=40 | | 49x-16x^3=0 | | -2=(7y-8y)2+14 | | (9n+4)+(3n^2-0.75)=180 | | -5h-13=-28 | | x^2-70=7x | | -x+5=2(x-8) | | 10x-6=3x-5 | | W-26=12 | | 9x+6y=n | | N+3=15-6 | | 3x-435=2425 | | 32+x+x+90=180 | | -4y+15=39 | | 0=x^2-5x-6.67 | | 8(x-2)+5=6x+2(-4+x) | | 5(x-3)+6=5x+9 | | 9y=6y+36 | | (6x-1)+(13+13)=90 | | 2x^2+8x-46=0 | | (7+m)+m=35 | | An=-5n-5 | | 6=m-39 | | 8x+20=6x+34 | | 2x^2-16+15=0 | | 15=5x+2y | | 4x+30+=5x+10 | | Z-17=-5 | | (6x-1)+(9+9)=90 | | 9(2x+3)=y | | -3y+5=-3y-9 |